ENTREPRENEURSHIP STRATEGY BASED ON CREATIVITY AND PRODUCT INNOVATION: AN EMPIRICAL STUDY ON THE SUSTAINABILITY OF BANYUWANGI TRADITIONAL BATIK MSMES - Nuraini, Viky; Hermawan, Haris; Rahayu, Jekti (Dynamic Management Journal, 2025)
Banyuwangi Batik as a cultural heritage faces the challenge of global competition, where creativity, product innovation, and entrepreneurial competence are the determinants of the sustainability of MSMEs. However, previous research has not comprehensively integrated these three factors in the context of traditional batik artisans. This study aims to analyze the influence of creativity, product innovation, and entrepreneurial competence on the success of Banyuwangi batik MSMEs, using explanatory research methods and a saturated sample of 46 respondents. Data were collected through questionnaires and analyzed using instrument tests, classical assumptions, multiple linear regression, and coefficient of determination (R²). The results showed that the three variables had a positive and significant effect (p < 0.05) with a contribution of 70% to business success, while 30% were influenced by external factors. The novelty of the research lies in an integrative approach in the context of traditional batik that combines aspects of design creativity with innovations based on local wisdom. These findings provide a theoretical contribution to culture-based and practical entrepreneurial literacy for MSME actors in developing competitive strategies.